Theoretical Studies as the Foundation for Formulating Research Hypotheses - Bayu Bambang Nur Fauzi; Arvial Ilham Fahrul Syah; Fajar Cahya Ramadhan; Muhammad Hisan Mubarok (Bibliotheca: Journal of Philosophy, 2026)
In any scientific research, theoretical studies and hypotheses are two crucial components that determine the direction and level of validity of the research. Theoretical studies serve as the basis for conceptual understanding for studying the phenomena under study, through systematically structured concepts, definitions, and statements. Meanwhile, hypotheses are tentative statements based on theoretical studies and must be verified through empirical data. However, in the academic world, hypotheses are often found that do not align with theoretical studies, thus reducing the credibility of the research. This article aims to conceptually discuss the role of theoretical studies as a basis for formulating research hypotheses. The discussion focuses on the meaning of theoretical studies, the function of hypotheses, and the relationship between the two in the scientific thinking process. The method used is a literature review, analyzing various relevant literature. The results show that a well-organized and in-depth theoretical study can produce logical, focused hypotheses based on strong scientific evidence, thus supporting theoretical consistency and the validity of the research method.